Application of continuous H2O2/UV advanced oxidative process as an option to reduce the consumption of inputs, costs and environmental impacts of textile effluents. (10th February 2020) - Rosa, Jorge Marcos; Tambourgi, Elias Basile; Vanalle, Rosangela Maria; Carbajal Gamarra, Félix Martin; Curvelo Santana, José Carlos; Araújo, Mauricio Campos
Abstract: Traditional textile wastewater treatment methods are inefficient and consequently pollute the environment. Thus, the use of new and efficient wastewater treatment techniques should be encouraged, such Advanced Oxidative Process (AOP), that is a fast and effective technique in the degradation of contaminants, which use strong oxidising agents in the degradation of organic contaminants, forming mainly into CO2 and water. This work aimed to apply H2 O2 /UV advance oxidative process (AOP) as an alternative to reduce inputs, costs and environmental impacts of textile effluents. Environmental cost accounting was used to demonstrate the economic, environmental and social gains of the process. The cotton fabrics were dyed with reactive dyestuffs in fourteen different colours. All dyeings were conducted according to formulations commonly used in the Brazilian industry. The efficiency of the dyestuff decomposition and the whiteness index of the reuse water were measured in each treated effluent. In addition, total organic carbon and the salt concentration were measured in the fifteenth effluent and compared to the Brazilian environmental standards, in order to know what effect of it when being discharged into the environment. Results show a removal efficiency of the total organic carbon and salt, 93% and 95% respectively, a consumption of sodium carbonate and sodium hydroxide were reduced by 33.21% and 25.51%, respectively. These results were influenced by the adsorption of the chemicals during the dyeing of the tissues and the UV/H2 O2 AOP. In additional, an average water consumption of 23.33 L kg −1 fabric dyed after fifteen dyeing, which is corresponding a saving of 92.86% of water and a total reduction in process costs of 22.47%. In this way, this work contributes to the sustainable development of new methods in order to be applied in textiles dyeing room. The water and chemicals decrease and adequacy of the effluent to the environmental norms reduced their environmental impacts and costs and improve the company image before society and their shareholders. Highlights: Reuse of water in fifteen dyes after effluent treatment. High savings by reducing water and chemical consumption. An AOP application in an industrial plant with high dyestuff degradation efficiency. A good example of applying environmental cost accounting.